Writing strategies of Saudi Arabian ESP learners : competence, apprehension and the role of strategy instruction - Alnufaie, Mohammad Rajab (Trinity College (Dublin, Ireland). School of Education, 2014)
This study explores the writing strategies of 121 second-year undergraduate Saudi student writers who are studying English as a foreign language and for specific purposes in one of the Saudi industrial colleges: Jubail Industrial College (JIC). The writing strategies under investigation were classified into two categories (process- oriented writing strategies and product-oriented writing strategies) based on their instructional philosophies.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin